Male genitalia morphology and dichotomous key of the Neotropical genera of Abracrini (Orthoptera: Acrididae: Ommatolampidinae) grasshoppers - Da Costa, Maria Kátia Matiotti; Carvalho, Gervásio Silva; Zefa, Edison (Zootaxa, 2022)
The comparative analysis of the internal and external male genitalia of the Abracrini grasshoppers was conducted, including representatives of the type species of the genera, specimens compared with the same or more representative specimens of the genus, and bibliography data. We include schematic illustrations that point to the morphological differences between the genitalia, based on subgenital plate, furculae, epiproct, cerci, ectophallic sheath, aedeagal valves, expansion of gonopore and epiphallus. A dichotomous key to the 21 Abracrini genera was presented.